A review of greenhouse gas emission profiles, dynamics, and climate change mitigation efforts across the key climate change players. (10th October 2019) - Zheng, Xiaosong; Streimikiene, Dalia; Balezentis, Tomas; Mardani, Abbas; Cavallaro, Fausto; Liao, Huchang
Abstract: The main objective of this study is to analyze and compare greenhouse gas emission profiles, dynamics thereof, and the climate change mitigation efforts of the major players in the global climate change arena, namely the G7 and BRICS countries that are accounting for more than 60% of the world greenhouse gas emissions as in 2017. Given that the energy sector is the major source of the greenhouse emissions in these countries, the framework of sustainable energy development indicators was applied to the comparative analysis. The analysis revealed the differences among the groups of countries in terms of greenhouse gas emission profiles and development trends of these profiles. The convergence of greenhouse gas emission profiles can be noticed between G7 and BRICS countries during 1990–2017 period. Greenhouse gas emissions per capita has decreased in G7 countries and increased in BRICS countries. Energy intensity, economic growth and carbon factor are the main drivers of greenhouse gas emissions per capita growth in both groups of countries. Carbon factor represents carbon intensity of a country's energy sector and is measured by greenhouse gas emissions per unit of total primary energy supply. The impact of carbon factor was least significant among the main drivers in both groups. Energy intensity was the major driver of decrease in greenhouse gas emissions per capita for both groups, however, the economic growth exceeded the contribution of energy intensity in BRICS countries and greenhouse gas emissions have increased in this group during investigated period. The comparative analysis of greenhouse gas emission profiles development trends and the main drivers of these trends in both groups of countries provides important insights in shaping future climate change mitigation policies and developing greenhouse gas emission reduction targets. Due to the high greenhouse gas profiles, low GHG reduction commitments and insufficient climate change mitigation the Perform, Achieve and Trade (PAT) scheme in India efforts in both groups there is danger of postponing implementation of Paris commitments and achieving the 1.5° target. The policies implemented in high ranked countries, like or Integrated Resources Planning in South Africa or measures under Energy efficiency directive in EU can be applied in low ranked countries by providing the substantial contribution to the country's climate targets. Graphical abstract: Image 1 Highlights: The GHG profiles of G7 and BRICS were converging during 1990–2017. GHG/capita has decreased in G7 countries and increased in BRICS countries. Energy intensity, economic growth and carbon factor - the main drivers of GHG/capita. Energy intensity - the major driver of decrease in GHG/capita for both groups. However, the economic growth exceeded the contribution of energy intensity in BRICS.